Burmanaglaea a new genus and Burmanaglaea felix, a new species from Myanmar (Lepidoptera, Noctuidae, Xylenini) - Benedek, Balázs; Babics, János; Volynkin, Anton V.; Saldaitis, Aidas (Zootaxa, 2020)
The tribe Xylenini Guenée, is especially rich in the Himalayan region with the highest diversity occurring during the late fall and winter. Exploration of this fauna has a rich history but became especially intensive during recent decades resulting in many new descriptions. Milestones in this vast territorial study by country include Pakistan (Ronkay & Ronkay 1999), India (Hacker 1992), Nepal (Hreblay & Ronkay 1998, Benedek et al. 2013), Taiwan (Hreblay & Ronkay 1997; 2000, Ronkay & Ronkay 2000) Thailand, Vietnam (Hreblay et al. 1999) and China (Ronkay et al. 2010, Benedek et al. 2012; 2013). To this list we now add the mountainous areas of Myanmar which have only recently become accessible. During a late fall collecting trip to Western Myanmar, three specimens of a strange looking noctuid species externally somewhat similar to the Western Himalayan Mniotype leucocyma (Hampson, 1907) were collected. After examination of its male and female genitalia, this species was proven to be new to science. Moreover, the male genitalia of the new species show a surprisingly unusual complex of features, some of which, together with the female genitalia, are characteristic and decisively significant to the subtribe Xylenina. The male and female genitalia of this species are most similar to those of the genera Eupsilia Hübner and Owadaglaea Hacker & Ronkay, however, these genitalia have certain autapomorphic characters which clearly justify separation on generic level. The description of the new genus and species is given below with a comparison to the related Eupsilia and Owadaglaea, several other related genera (Lithophane Hübner, Conistra Hübner and Xylena Ochsenheimer) and the externally similar M. leucocyma as well.